Common Sharks of Florida - Florida Sea Grant (EDIS)
Florida’s shark population is diverse and includes species that range in size from only a few feet to more than 40 feet in total length. The following species are among the most common. This revised 3-page fact sheet was written by Florida Sea Grant, and published by the UF Department of Sea Grant, December 2011.